Symptom evaluation in reflux disease: workshop background, processes, terminology, recommendations, and discussion outputs. (13th April 2004) - Dent, J; Armstrong, D; Delaney, B; Moayyedi, P; Talley, N J; Vakil, N
Abstract : There has been no published indepth systematic evaluation of the best approaches to symptom evaluation in gastro-oesophageal reflux disease (GORD). A two day international multidisciplinary workshop was therefore held in Marrakech, Morocco, in September 2002 to address these issues. The aim of the workshop was to critically review the data regarding the reliability, processes, and priorities for symptom evaluation in GORD patients. The workshop was designed to give outputs that could be readily reported and to arrive at specific recommendations on best practice in symptom evaluation in reflux disease.